Johnny Cash and the paradox of American identity - Edwards, Leigh H., 1970- (Profiles in popular music., 2009)
From the Publisher: Throughout his career, Johnny Cash has been depicted-and has depicted himself-as a walking contradiction: social protester and establishment patriot, drugged wildman and devout Christian crusader, rebel outlaw hillbilly thug and elder statesman. Leigh H. Edwards explores the allure of this paradoxical image and its cultural significance. She argues that Cash embodies irresolvable contradictions of American identity that reflect foundational issues in the American experience, such as the tensions between freedom and patriotism, individual rights and nationalism, the sacred and the profane. She illustrates how this model of ambivalence is a vital paradigm for American popular music, and for American identity in general. Making use of sources such as Cash's autobiographies, lyrics, music, liner notes, and interviews, Edwards pays equal attention to depictions of Cash by others, such as Vivian Cash's publication of his letters to her, documentaries and music journalism about him, Walk the Line, and fan club materials found in the archives at the Country Music Foundation in Nashville, to create a complete, albeit fragmented, portrait of Cash and his significance as a cultural icon.